2017
DOI: 10.1038/srep41312
|View full text |Cite
|
Sign up to set email alerts
|

The choreography of the chemical defensome response to insecticide stress: insights into the Anopheles stephensi transcriptome using RNA-Seq

Abstract: Animals respond to chemical stress with an array of gene families and pathways termed “chemical defensome”. In arthropods, despite many defensome genes have been detected, how their activation is arranged during toxic exposure remains poorly understood. Here, we sequenced the transcriptome of Anopheles stephensi larvae exposed for six, 24 and 48 hours to the LD50 dose of the insecticide permethrin to monitor transcriptional changes of defensome genes across time. A total of 177 genes involved in insecticide de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…Exposure to insecticide instigates a complex response through which insects sequester, detoxify or excrete toxins before they reach their target or have other adverse consequences. The battery of detoxification genes and those elements which control their coordinated response has been labelled the defensome [1]. The insect defensome must cope with a variety of assaults from foodstuffs e.g.…”
mentioning
confidence: 99%
“…Exposure to insecticide instigates a complex response through which insects sequester, detoxify or excrete toxins before they reach their target or have other adverse consequences. The battery of detoxification genes and those elements which control their coordinated response has been labelled the defensome [1]. The insect defensome must cope with a variety of assaults from foodstuffs e.g.…”
mentioning
confidence: 99%
“…The higher number of significantly DEGs identified in Pierce population when compared to Clarke population flies correlates with the higher LC 50 values calculated for Pierce county flies. DEGs could reflect a combination of a selective effect yielding gene transcripts enriched in flies surviving the insecticide treatment, and an inductive effect, referred to as the defensome which occurs in animals during the treatment period in response to toxicants (Niu et al, 2012;De Marco et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Azadirachta indica and other Meliaceae species have shown strong larvicidal, antiemergence, repellency, and antioviposition effects in different mosquito species (Mulla and Su 1999). It is now known that, in several mosquito species, part of the detoxification process against xenobiotics is mediated by adenosine triphosphatebinding cassette (ABC) transporters on Anopheles stephensi Liston (Epis et al 2014a(Epis et al , 2014bPorretta et al 2016;De Marco et al 2017;Mastrantonio et al 2017); Anopheles gambiae Giles (Nkya et al 2014); Aedes aegypti (L.) (Bariami et al 2012); and Aedes albopictus (Skuse) (Esquivel et al 2016). In particular, on An.…”
mentioning
confidence: 99%
“…In particular, on An. stephensi it has been demonstrated that, among the 8 subfamilies (from A to H) of ABC transporters existing in insects, the B and G subfamilies play a major role in the detoxification of permethrin, showing a pattern of response that varies with time (Epis et al 2014a(Epis et al , 2014bDe Marco et al 2017;Mastrantonio et al 2017). Despite their importance against pyrethroids, these genes are not differentially expressed in response to larval exposure to temephos, a widely used larvicide, highlighting an insecticide-specific involvement of the transporters in this mosquito species (Porretta et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation